Data on optical coherence tomography guidance for the management of angiographically intermediate left main bifurcation lesions - Ilaria Dato (Data in Brief, 2017)
The data presented in this article are related to the research article entitled “Optical coherence tomography guidance for the management of angiographically intermediate left main bifurcation lesions: early clinical experience” [1]. In this article we reports details about our clinical experience with frequency domain-optical coherence tomography (FD-OCT) guidance for the management of patients with left main (LM) bifurcation lesions of intermediate angiographic severity. LM patients were assessed by FD-OCT and, on the bases of the findings, managed by myocardial revascularization or conservative treatment (revascularization deferral). The observed outcomes support the feasibility of FD-OCT guidance for LM bifurcated lesions and call for further clinical evaluations in appropriately designed prospective studies.